Theoretical Fundamentals of International Economic Integration - Dimova, Ruska (Research Papers, 2007)
The study treats the development in the theoretical foundations of international economic integration. In the beginning of the XXI-st century the theoretical framework of international economic integration consists of the liberal social model, the economic globalization and the regionalism. The new, second phase of international integration deals with the quality of the process of the global regionalism. The global economic integration is defined by a set of concepts including international economic community, market-led integration, interregional integration, integration area, regional integration cooperation etc. Its form and stages are different. But its global organizational structures and components are similar. The institutional advantages of international economic communities outline in the source of the new institutionalism are the leading factors in the process of convergence in the economical, political and cultural spheres. Examples of implications of the new theoretical framework of international integration are global coordination, enhanced cooperation and interregional integration. A supported thesis in the study is that the future of international economic communities is the building of regional and global structures for government of free market, political and cultural interconnections between integrated nations and implement of policies and strategies of mutual win-win benefits.The study will be useful for those, who are interested in the problems of international integration. The understanding of global economic integration is very important in view of the forthcoming full membership of Bulgaria in the European Union beginning on 01.01. 2007.